Clínica artivista decolonial: corpos-telas em cenas sociais, storyboards crips e produção de diferenças - Pereira, José Arnaldo (2024)
Colonization is a phenomenon that generates oppression, exclusion and injustice, acting through the suppression of differences and bodies that do not fit into hegemony. With this in mind, psychology, artivism and decoloniality can establish alliances to counter this system. From this perspective, the objective of this research is to track how different groups of people engage in artivist experiments. Furthermore, we seek to discuss the formation of artivism as a tool and how it can be integrated as a clinical practice and decolonial device. To achieve this, this research had as its method an alliance between Cartography, Performance and Artivism, as a positioning of social intervention, favoring the multiplication of modes of subjectivation, tensions, tools and social transformation, invested in experiments carried out with 10 participants. This research produced crip storyboards of the show and short scenes, made by participants in the artivist experimentation, highlighting in its production and formulation a collective aesthetic inscribed based on the participants' differences. As well, there was an invention of the body-screen notion in social scenes, signaled in 8 (eight) intensities, namely: Construction, distribution and reconfigurations of power; Mobilizations between Authority and Submission: A Look at the Dynamics of Power and Responsibility; About bodies and their particularities: the urgencies and priorities are different; Artivist experimentation, the tensions of being understood and other configurations of power; Did you plan to go wrong? The normative world plans for me, someone different, to be the mistake!; Artivist experimentation, production of imaginaries and unthought-of impossibilities, until then: if there is an opportunity, it is possible to invent!; How to mobilize differences in favor of meetings, listening and dialogue: attempts at experimentation; and When differences attribute aesthetics, how can normative ones feel?